THE IMPACT OF STRATEGIC MANAGEMENT ON INCREASING THE COMPETITIVENESS OF ENTERPRISES (Development Service Industry Management, 2024)
The article explores the importance of strategic management as a key factor for the successful functioning of enterprises in today’s competitive environment. Emphasis is placed on the necessity of a well-developed strategy that accounts for changes in external and internal environments, enabling adaptation to modern challenges. Strategic management is defined as a dynamic system encompassing planning, organization, coordination, motivation, and control. These functions form the foundation of effective enterprise management aimed at achieving long-term goals.Special attention is given to the cost reduction process as one of the strategic objectives. The stages of cost reduction include cost analysis, the development of effective control methods, the implementation of specialized programs, and the definition of long-term measures for optimizing expenses. It is highlighted that reducing costs, particularly material, depreciation, and commercial costs, enhances profitability while preserving employee motivation and maintaining production stability.The article also examines management in the context of weak signals and strategic uncertainties, enabling enterprises to respond promptly to challenges. An algorithm for identifying strategic tasks is proposed, considering political, economic, technological, and social aspects of the external environment. Mechanisms for crisis management and the role of specialized teams in ensuring business continuity are also discussed.The findings emphasize the significance of strategic management in enhancing competitiveness, stability, and adaptability of enterprises in a changing market environment. Effective strategy implementation not only allows the achievement of short-term goals but also ensures long-term development and access to global markets.
Keywords: strategic management; strategy planning; cost optimization; competitiveness; enterprise adaptation; environmental analysis; external environment; internal environment